Субстантивне вираження спортивних реалій у сучасній англійській мові - Василенко, Ольга Вікторівна; Лісінська, Тетяна Юріївна; Vasylenko, Olha V.; Lisinska, T. Yu. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджено проблему лінгвістичного вираження спортивних реалій. Спортивна термінологія перебуває в центрі уваги філософських, психологічних, соціологічних та лінгвістичних дискусій. Дослідження ґрунтується на тезаурусі Роже й представлено п’ятьма лексико-семантичними групами іменників. У роботі проаналізовано частоти іменників на позначення спортивних реалій, визначено високочастотні іменники та лексико-семантичні групи. The research is devoted to the problem of lexical realization of sport realia. Sport terminology is placed in the centre of philosophical, psychological, sociological and linguistic discussions. The research is based on the material of Roget’s thesaurus and is represented by 5 lexico-semantic groups of nouns. In the article the analysis of the frequency of the nouns denoting sport realia is conducted, the nouns with the highest frequency as well as lexico-semantic groups of nouns with the prevailing frequency in the general list are singled out. The results of the quantitative analysis showed that the highest quantity is characteristic to the nouns denoting competitive activity, social factor in sport and kinds of sport. The analysis of the vocabulary of all the 5 lexico-semantic groups of nouns showed the absence of the common nouns in either of them.
The Noun Representation of Sport Realia in Modern English
Keywords: спорт; sport; лексико-семантична група; lexico-semantic group; абсолютна частота; absolute frequency